2014
DOI: 10.1136/bmjopen-2014-005577
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a dual-ring wound protector for prevention of incisional surgical site infection after Whipple's procedure (pancreaticoduodenectomy) with preoperatively-placed intrabiliary stents: protocol for a randomised controlled trial

Abstract: IntroductionAmong surgical oncology patients, incisional surgical site infection is associated with substantially increased morbidity, mortality and healthcare costs. Moreover, while adults undergoing pancreaticoduodenectomy with preoperative placement of an intrabiliary stent have a high risk of this type of infection, and wound protectors may significantly reduce its risk, no relevant studies of wound protectors yet exist involving this patient population. This study will evaluate the efficacy of a dual-ring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Post-operative pancreatic anastomotic leak/fistula (POPF), delayed gastric emptying (DGE), bile leak and postpancreatectomy haemorrhage (PPH) were defined as per the International Study Group of Pancreatic Surgery (ISGPS) criteria [20][21][22]. Mortality was defined as any death that has occurred not only in the 30 days following surgery but even thereafter so long as there exists sufficient evidence to link the cause of death to the surgery or its complications.…”
Section: Definition Of Complicationsmentioning
confidence: 99%
“…Post-operative pancreatic anastomotic leak/fistula (POPF), delayed gastric emptying (DGE), bile leak and postpancreatectomy haemorrhage (PPH) were defined as per the International Study Group of Pancreatic Surgery (ISGPS) criteria [20][21][22]. Mortality was defined as any death that has occurred not only in the 30 days following surgery but even thereafter so long as there exists sufficient evidence to link the cause of death to the surgery or its complications.…”
Section: Definition Of Complicationsmentioning
confidence: 99%
“…A recent meta‐analysis including 1,008 patients demonstrated that wound protector reduced the rates of SSIs after gastrointestinal and biliary surgery . A randomized controlled trial evaluating the efficacy of wound protector in PD is currently underway and results are forthcoming . The lack of level I recommendations may explain the low number of surgeons currently using wound protector (30%).…”
Section: Discussionmentioning
confidence: 99%
“…Given randomized controlled clinical trial data suggesting the use of wound protectors in patients with preoperative biliary stents to be protective against surgical site infection, we planned an additional stratified analysis by use of preoperative biliary stents, either internal endoscopic stents or external percutaneous stents. 3,7 Outcome of interest The primary outcome of interest was defined as either superficial or deep SSI within 30 days. Superficial SSIs are characterized by postoperative cellulitis, typically involving only the skin or subcutaneous tissues for which antibiotic therapy is administered.…”
Section: Intervention Of Interestmentioning
confidence: 99%
“…3 To date, there are two randomized controlled clinical trials evaluating the effect of wound protectors on SSI in patients undergoing PD that have published conflicting results. 3,7,8 In one randomized controlled trial from Canada, wound protectors significantly decreased the incidence of superficial or deep SSI with a relative risk reduction of 52% in patients undergoing elective PD who had preoperative biliary stents. 3 In the other randomized controlled trial from Italy, wound protectors did not reduce the risk of superficial SSI following PD in patients with or without preoperative biliary stent placement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation